Why cash alone won’t solve Japan’s baby deficit - Takao, Yasuo (Crawford School of Public Policy in the ANU College of Asia & the Pacific at The Australian National University, 2024)
Record low birth rates in Japan have led Prime Minister Fumio Kishida to allocate as much as 3.6 trillion yen (US$22.3 billion) per annum in an attempt to reverse the trend. But fertility-boosting policy measures have historically had limited success due to the country’s conservative family values and dwindling interest in marriage and childrearing among young people. An effective response to the crisis will require the Japanese government to adapt its policies to reflect evolving societal norms and to better support diverse family structures.